Ultrasound‐Assisted Thermal Maceration of Bordo Grape (Vitis labrusca L.): Insights of Anthocyanin Degradation Kinetics, Antioxidant Activity and Thermostability Parameters - de Almeida, Micael José [UNESP]; Ribeiro‐Sanches, Marcio Augusto [UNESP]; Guimarães, Bianca; Lago‐Vanzela, Ellen Silva [UNESP]; Telis‐Romero, Javier [UNESP] (Wiley, 2025)
ABSTRACT This study assessed the degradation kinetics of monomeric anthocyanins in Bordo grape must after conventional thermal maceration (CV) and thermosonication (TS) at temperatures ranging from 20°C to 90°C. Quality analysis of the musts included measurements of soluble solids (SS), pH, titratable acidity (TA), and color ( L *, a *, b *, , , and ). Kinetic parameters, including half‐life ( t 1/2 ), decimal reduction time ( D ), temperature coefficient ( Q 10 ), and decimal reduction temperature ( z ), along with thermodynamic parameters such as activation enthalpy (Δ H # ), Gibbs free energy (Δ G # ), and activation entropy (Δ S # ), were determined. Antioxidant capacity was evaluated using ABTS, DPPH, and FRAP methods after maceration and heat treatment. TS did not significantly affect pH and TA but increased SS, resulting in a higher SS/TA ratio and greater total anthocyanin content. Color parameters indicated that TS produced a darker must. The degradation followed first‐order kinetics, with rate constants ranging from 8.18 × 10 −6 to 1855.00 for TS and 8.89 × 10 −6 to 2070 × 10 −6 (min −1 ) for CV, showing significant differences. TS reduced activation energy and Δ H # , with positive Δ G # confirming the non‐spontaneous nature of degradation and lower Δ S # indicating greater molecular stability. Despite the significant differences in kinetic and thermodynamic parameters between the methods, the practical impact is minimal, suggesting that anthocyanins extracted by TS have similar thermal stability to those obtained by CV. Antioxidant tests revealed that TS initially increased antioxidant capacity due to extraction, although antioxidant activity decreased with higher temperatures. Despite this, TS must showed higher antioxidant capacity post‐thermal treatment compared to CV. These results suggest that TS is an effective method to increase the extraction of anthocyanins from Bordo grape, without negatively affecting their thermal degradation kinetics, thermodynamic, and stability parameters.